The Implementation of Street Vendor Relocation Policy in the Pro-Environmental Era in Mojokerto City Square - Andy Fefta Wijaya; Fadel Muhammad; Marta Trifena Patriot; Asti Amelia Novita (Pusbindiklatren Bappenas, 2021)
Street vendors are one of the informal sectors that often cause problems in urban areas, such as the street vendors in Mojokerto City Square. The presence of street vendors is considered to have disturbed the orderliness and cleanliness of the city environment. Therefore, based on the Local Government Regulation of Mojokerto City No. 5 of 2005 concerning the Arrangement and Development of Street Vendor Activities, the government implemented a policy of street vendor relocation. This paper aims to analyze the implementation of street vendor relocation policy in the area of ​​Mojokerto City square. This research uses a descriptive qualitative approach involving six key informants with interviews and documentation as the data collection method. This study indicates that implementing the street vendors relocation policy in the square area of ​​Mojokerto City is not entirely effective. Four factors influence the implementation of the policy, communication, resources, disposition, and bureaucratic structure.